Tipologi Komunikasi Virtual: Studi Kasus Pada Facebook Parenting Indonesia - Cheryl Pricilla Bensa (Universitas Multimedia Nusantara, 2015)
In the era of new media, social media is one of the tools that are used by the mass media to develop and expand target readers. Target readers, developed through social media usually called virtual communities. Virtual communities have been utilized by the media to expand their target market. Parenting Indonesia has decided to also establish a virtual community for its readers. Based on Porter's theory community typology, researcher analyzes five attributes of typology in Parenting Indonesia's virtual community on Facebook. The concepts analyzed in this study are New Media, Social Media, Social Networking, Virtual Community and Typology of Virtual Community. Research methodology used in this research is a case study with qualitative approach, the paradigm of post-positivist, and descriptive type. The data collection techniques are interviews and participant observation. The results show that Parenting Indonesia's virtual community on Facebook has this following typology: participants have similar interests in parenting information and have elements of social function, exist within virtual environments only, has a hybrid platform (asynchronous and synchronous), including public interaction that are strong and intense, and used to seek profit. Keywords: virtual community, new media, social media, a typology of virtual community